The Role of Emotional States on Purchase Decision-Making among Novice Stock Investors - Joshua Antonius Dardana; Honey Wahyuni Sugiharto Elgeka (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Novice stock investors tend to make investment decisions based on their emotions, so they usually have lower performance. Emotions can affect decision-making through immediate emotions (emotional states) and expected emotions (emotional consequences). Happy and sad are the strongest emotions. Therefore, this research aims to examine and explain the effect of emotional states, specifically happy and sad, on novice stock investors' purchase decision-making. This research uses the experiment method, with 30 novice stock investors divided into three groups (two experimental and one control group). The result shows no effect between happy and sad emotional states on purchase decision-making (p > 0,05). The result is caused by participants' tendencies to make rational decisions for the highest utility. The higher the utility they get, the happier they will be, and vice versa. Thus, happy and sad emotions act as expected emotions, not as immediate emotions in decision-making.